2016
DOI: 10.1186/s40538-016-0080-6
|View full text |Cite
|
Sign up to set email alerts
|

An effective bioremediation approach for enhanced microbial degradation of the veterinary antibiotic sulfamethazine in an agricultural soil

Abstract: Background:The veterinary antibiotic Sulfamethazine (SMZ) contaminates soils via manure applications. Like other soil contaminants (herbicides, fungicides, and nematicides), it has to be degraded. The main challenge is that SMZ biodegradation with bacteria is impeded, since SMZ is a bacteriostatic antibiotic, designed to block microbes in their growth. Results:In this study, we enriched the indigenous soil microbial community (including the single strain Microbacterium sp. C448, adapted to SMZ degradation) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 45 publications
(82 reference statements)
1
15
0
1
Order By: Relevance
“…This indicates that the sad cluster as a whole might be mobile with a potential to spread as a resistance determinant. The potential of this cluster to act as a resistance determinant should be kept in mind when testing antibiotic mineralizing strains for bioremediating contaminated soils or waters 44 , 45 . It has recently also been reported by Vila-Costa et al .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the sad cluster as a whole might be mobile with a potential to spread as a resistance determinant. The potential of this cluster to act as a resistance determinant should be kept in mind when testing antibiotic mineralizing strains for bioremediating contaminated soils or waters 44 , 45 . It has recently also been reported by Vila-Costa et al .…”
Section: Resultsmentioning
confidence: 99%
“…Higher values of the measured parameters suggest that the introduced bacterial strain had the ability to survive in new conditions and increased the catabolic potential of the microbial community. Many studies on the degradation of pollutants in the soil environment showed synergy between inoculated strains and natural soil microflora, which resulted in the accelerated degradation of pollutants [39][40][41]. However, the lack of any effect of the introduction of bacterial strains into the soil was also observed.…”
Section: Resultsmentioning
confidence: 99%
“…strain BR1. [52][53][54][55]. They all have the ability of degrading sulfonamides, which can provide a new insight toward sulfonamide biodegradation [56].…”
Section: Discussionmentioning
confidence: 99%